Stereochemical and structural effects of (2R,6R)-hydroxynorketamine on the mitochondrial metabolome in PC-12 cells - Faccio, Andréa T.; Ruperez, Francisco J.; Singh, Nagendra S.; Angulo, Santiago; Tavares, Marina F.M.; Bernier, Michel; Barbas, Coral; Wainer, Irving W. (Biochimica et biophysica acta, 2018)
Impairment in mitochondrial biogenesis and function plays a key role in depression and anxiety, both of which being associated with changes in fatty acid and phospholipid metabolism. The antidepressant effects of (R,S)-ketamine have been linked to its conversion into (2S,6S;2R,6R)-hydroxynorketamine (HNK); however, the connection between structure and stereochemistry of ketamine and HNK in the mitochondrial homeostatic response has not yet been fully elucidated at a metabolic level. We used a multi-platform, non-targeted metabolomics approach to study the change in mitochondrial metabolome of PC-12 cells treated with ketamine and HNK enantiomers. The identified metabolites were grouped into pathways in order to assess global responses. Treatment with (2R,6R)-HNK elicited the significant change in 49 metabolites and associated pathways implicated in fundamental mitochondrial functions such as TCA cycle, branched-chain amino acid biosynthetic pathway, glycoxylate metabolic pathway, and fatty acid β-oxidation. The affected metabolites included glycerate, citrate, leucine, N,N-dimethylglycine, 3-hexenedioic acid, and carnitine and attenuated signals associated with 9 fatty acids and elaidic acid. Important metabolites involved in the purine and pyrimidine pathways were also affected by (2R-6R)-HNK. This global metabolic profile was not as strongly impacted by treatment with (2S,6S)-HNK, (R)- and (S)-ketamine and in some instances opposite effects were observed. The present data provide an overall view of the metabolic changes in mitochondrial function produced by (2R,6R)-HNK and related ketamine compounds and offer an insight into the source of the observed variance in antidepressant response elicited by the compounds. [Display omitted] •(2R,6R)-HNK produced significant changes in mitochondrial pathways.•(2S,6S)-HNK, (R)-ketamine and (S)-ketamine yielded different effects.•Results reflect difference in antidepressant response elicited by the compounds.•A new hypothesis describing the antidepressant response produced by (2R,6R)-HNK